Corneal Epithelial "Neuromas": A Case of Mistaken Identity?. Issue 7 (July 2020) - Stepp, Mary Ann; Pal-Ghosh, Sonali; Downie, Laura E.; Zhang, Alexis Ceecee; Chinnery, Holly R.; Machet, Joshua; Di Girolamo, Nick
Abstract : Abstract: Laser scanning in vivo confocal microscopy is a useful clinical tool to assess the corneal nerves in human and laboratory animals. With this new technology, the use of terms such as "neuromas" and "microneuromas" is becoming popular to describe nerve structures seen in humans. Here, we point out that the sites where stromal nerves enter the corneal epithelium are often hyperreflective and can appear dysmorphic when imaged using in vivo confocal microscopy. Furthermore, we clarify what is known anatomically about how the nerves enter the corneal epithelium from the stroma, and we urge colleagues to differentiate between hyperreflective foci at the corneal stromal–epithelial nerve penetration sites and alterations in nerve morphology secondary to injury or disease.